Small Groups, Big Impact: Eliminating Li+ Traps in Single-Ion Conducting Polymer Electrolytes - Kristina Borzutzki; Dengpan Dong; Christian Wölke; Margarita Kruteva; Annika Stellhorn; Martin Winter; Dmitry Bedrov; Gunther Brunklaus (iScience, 2020)
Summary: Single-ion conducting polymer electrolytes exhibit great potential for next-generation high-energy-density Li metal batteries, although the lack of sufficient molecular-scale insights into lithium transport mechanisms and reliable understanding of key correlations often limit the scope of modification and design of new materials. Moreover, the sensitivity to small variations of polymer chemical structures (e.g., selection of specific linkages or chemical groups) is often overlooked as potential design parameter. In this study, combined molecular dynamics simulations and experimental investigations reveal molecular-scale correlations among variations in polymer structures and Li+ transport capabilities. Based on polyamide-based single-ion conducting quasi-solid polymer electrolytes, it is demonstrated that small modifications of the polymer backbone significantly enhance the Li+ transport while governing the resulting membrane morphology. Based on the obtained insights, tailored materials with significantly improved ionic conductivity and excellent electrochemical performance are achieved and their applicability in LFP||Li and NMC||Li cells is successfully demonstrated.